THR-α and THR-β gene profiling and characterization of Gelidiella acerosa extract binding and uptake by 3,3′,5-TRIIODO-L-THYRONINE Stimulated NIH3T3 cell line - Darsana Panchalingam; Dhanalakshmi Balasubramanium; Satish Lakkakula; Jegatheeswaran Sonamuthu; Indhirakumar Balakrishnan (The Bioscan, 2025)
The marine resources, macro-algae raw materials have gained much attention as they exhibit a great applicability as dietary ingredients and being highlighted as a potential source of bioactive compounds. Thyroid issues in India are likely due long standing iodine deficiency in the diet. This investigation was to assess the antithyroid activities of the macroalgae Gelidiella acerosa. Macroalgae extract characterized for the presence of antithyroid compound confirmed the presence of pharmaco-bioactive compounds were confirmed. Further, the highly sensitive NIH3T3 fibroblast cell line was stimulated with 3,3′,5-Triiodo-L-thyronine (T3) - an active thyroid prohormone to confirm the binding and expressing capacity of the active alga extract fraction for the THR-α and β gene expression. The results indicate that Gelidella acerosa treatment led to higher expression levels of thyroid hormone receptors compared to the control. Thyroid hormone receptor expression in the cell line, contributing to its potential as a regulatory agent in thyroid function. Marine red algae, Cell line, Proactive hormone, Characterization, Gene profiling